Pharmacist-driven penicillin skin testing service for adults prescribed nonpreferred antibiotics in a community hospital. (31st October 2019) - Englert, Ethan; Weeks, Andrea
Abstract: Purpose: Results of a study evaluating the implementation and impact of a pharmacist-driven penicillin skin testing (PST) service for patients prescribed alternative antibiotics in the community hospital setting are reported. Methods: A prospective pilot service in which patients with a documented penicillin allergy (type I, immunoglobulin E [IgE]–mediated) who were prescribed alternative antibiotics received PST by a trained pharmacist was implemented; if test results were negative, the allergy was de-labeled from their electronic medical record. The primary objective was the percentage of patients switched to first-line antibiotics. Secondary objectives included length of stay (LOS) and inpatient antimicrobial costs to the health system. Results: Twenty-two patients were proactively identified and received PST by a pharmacist. Of those tested, all were negative, with no type I (IgE-mediated) hypersensitivity reactions to the test itself or to the beta-lactam antibiotic administered thereafter; 68.2% (15/22) were successfully transitioned to a beta-lactam after PST. As a result, a decrease in the use of fluoroquinolones and vancomycin and an increase in use of narrow penicillin-based antibiotics and first- and second-generation cephalosporins were observed. The mean ± S.D. LOS per patient was 7.41 ± 6.1 days, and the total cost of inpatient antimicrobial therapy to the health system was 1, 698.88. Conclusion: A pharmacist-driven PST service was successfully implemented in a community hospital setting.